2008
DOI: 10.1007/s10483-008-0807-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of natural convection heat transfer from a fin by triangular perforation of bases parallel and toward its tip

Abstract: This study examines the heat transfer enhancement from a horizontal rectangular fin embedded with triangular perforations (their bases parallel and toward the fin tip) under natural convection. The fin's heat dissipation rate is compared to that of an equivalent solid one. The parameters considered are geometrical dimensions and thermal properties of the fin and the perforations. The gain in the heat transfer enhancement and the fin weight reduction due to the perforations are considered. The study shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The number of perforations also becomes the main feature in increasing the perforation to the plate fin. Al-Essa and Al-Odat [9] examined the effect of triangular perforations on the heat transfer performance of a plate fin exposed to natural convection. They confirmed that they had optimum drilling size and optimum gap values.…”
Section: Introductionmentioning
confidence: 99%
“…The number of perforations also becomes the main feature in increasing the perforation to the plate fin. Al-Essa and Al-Odat [9] examined the effect of triangular perforations on the heat transfer performance of a plate fin exposed to natural convection. They confirmed that they had optimum drilling size and optimum gap values.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of perforating plate fins for natural convection heat transfer has also been considered in a number of previous studies. Alessa and Al-Widyan [33], Alessa et al [34] and…”
Section: Introductionmentioning
confidence: 99%
“…They have shown different flow patterns are dependent on fluid flow rates. AIEssa and colleagues studied the heat dissipation from a horizontal rectangular fin with square perforation, rectangular perforations with an aspect ratio of two, equilateral triangular perforations of bases parallel and towards its fin tip by using the finite element technique under natural convection. They compared results between the perforated fin and its external dimensionally equivalent solid fins.…”
Section: Introductionmentioning
confidence: 99%